Global methods for combinatorial isoperimetric problems - Harper, Lawrence H. (Lawrence Hueston), 1938- (Cambridge studies in advanced mathematics, 2004)
Based on Professor Harper's substantial experience in teaching global methods in combinatorial optimisation and is ideal for graduate students entering the field as well as experienced researchers. The author has increased the utility of the text for teaching by including worked examples, exercises and material about applications to computer science.